Assessing the Quality of services provision in the system of Bus Rapid Transit from the viewpoint of citizens Case study: Rasht city - Seyedreza Azadeh; fatemeh Alavi Zadeh Shalkouhi (تحقیقات کاربردی علوم جغرافیایی)
The main goal of this research is to measure the quality of services in the Rasht city BRT from the citizen's point of view. In this regard, the research with respect to goal is practical and with respect to method is descriptive-analytical. A questionnaire technique was used to collect information. In this regard, 400 questionnaires were distributed, and in which 389 complete and error-free questionnaires were collected. After collecting questionnaires, the data were entered into SPSS software and analyzed by using statistical tests (one sample t test, factor analysis, and Cramer's V test). The results of the survey showed that out of the 389 respondents, 178 people (45.8%) evaluated the overall quality and efficiency of the BRT system in Rasht city at a moderate level and also 99 respondents (25.4%) evaluated the quality and efficiency of the BRT system in Rasht city at a desirable level. The average quality and overall efficiency score of the BRT system in Rasht city has been 2.87 out of the citizen's idea. The results of one-sample t-test indicate that there is a significant difference between the mean quality variable and overall efficiency of the BRT system in Rasht city with the test statistic. Based on the results of factors analyzes, 17 studied indicators are summarized in three factors. Based on the extracted factors, the first factor has the greatest impact on health and safety. The second factor has been the load factor on bus working hours, waiting time, cost of payment, total number of buses and distance between bus stations indicators. Finally, the third factor has its impact on cleanliness of buses, cooling system, heating system and the number of seats on buses. Using v Kramer test showed that there is a meaningful relationship between the five independent variables age variables, type of occupation and personal car ownership with dependent variable (quality and overall efficiency of BRT system in Rasht).